2014
DOI: 10.1007/s10488-014-0558-0
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Organizational Predictors of Pediatric Psychiatric Inpatient Admission in Connecticut Hospitals: A 6 Month Secondary Analysis

Abstract: The objective of this study is to test the hypotheses that bipolar disorders or depressive disorders, minority status, and the presence of pediatric inpatient psychiatric unit will be individual predictors of pediatric psychiatric inpatient admission, and to provide a model that will evaluate which individual and organizational characteristics predict pediatric psychiatric inpatient. For this purpose, a secondary analysis of the medical records of 1,520 pediatric patient visits between January 1, 2008 and June… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…We found major increases in affective disorders in subjects aged 13–18, including anxiety disorders, childhood affective disorders and depression. Depression is a major reason for CAP hospital admission [ 82 , 83 ] and readmission [ 84 ] among adolescents. The high prevalence of depression among our older age group may have been partly due to suicidality, which has been strongly associated with both depression [ 63 ] and inpatient admissions [ 26 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found major increases in affective disorders in subjects aged 13–18, including anxiety disorders, childhood affective disorders and depression. Depression is a major reason for CAP hospital admission [ 82 , 83 ] and readmission [ 84 ] among adolescents. The high prevalence of depression among our older age group may have been partly due to suicidality, which has been strongly associated with both depression [ 63 ] and inpatient admissions [ 26 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have identified demographic characteristics and clinical factors as predictors of voluntary admission of young patients seen in psychiatric crisis situations [15][16][17][18]. Demographic characteristics that were found to be associated with decisions to hospitalize children and adolescents after emergency consultation were relatively older age, minority status, and having been adopted [16][17][18][19]. Clinical factors that were associated with a higher chance of admission were suicide attempt or self-injurious behavior, the clinician's appraisal of high suicide risk, the presence of a depressive or bipolar disorder, the severity of psychiatric symptoms, comorbidity, a lower score on the global assessment of functioning (GAF), and prior admission.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical factors that were associated with a higher chance of admission were suicide attempt or self-injurious behavior, the clinician's appraisal of high suicide risk, the presence of a depressive or bipolar disorder, the severity of psychiatric symptoms, comorbidity, a lower score on the global assessment of functioning (GAF), and prior admission. The likelihood of hospitalization was also increased by a prior emergency consultation, substance abuse or dependence, and being on psychotropic medication [15][16][17][18][19]. However, both these demographic characteristics and the clinical factors cannot be modified to prevent emergency admissions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be that PES encounters involving these disorders are less severe or emergent than for primary psychotic disorders or substance use disorders. Research prior to the pandemic indicated that primary psychotic disorders are a significant predictor of inpatient admission in adolescents ( Huffman et al, 2012 ), and that youth psychiatric ED visits involving anxiety disorders and stress disorders are less likely to result in inpatient admission ( Hunter et al, 2015 ). In responding to anxiety or stress disorders, youth and families may have felt that risks related to COVID-19 outweighed the possible benefits of seeking PES.…”
Section: Discussionmentioning
confidence: 99%